Assessing corporate reputational damage due to collusion: an empirical approach - Wiggins, Vincent John (My University, 2017)
Event studies are widely used in finance and business research. The study involves identifying an event of interest, analysing the abnormal stock return and testing the significance of the event. This research assesses the change to a company’s stock value after an announcement of a collusive engagement. The study adopts an empirical approach by means of an event study analysis to determine the magnitude of the valuation change as well as other statistical methods to define the statistical significance of the valuation variation. The research also seeks to identify if the valuation change will always be negative, given the negativity associated with the collusive announcement
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management in Finance and Investment Johannesburg, 2017
Keywords: Stocks--Prices--Mathematical models; Capital market--South Africa